2013
DOI: 10.1017/jfm.2013.409
|View full text |Cite
|
Sign up to set email alerts
|

Vorticity moments in four numerical simulations of the 3D Navier–Stokes equations

Abstract: The issue of intermittency in numerical solutions of the 3D Navier-Stokes equations on a periodic box [0, L] 3 is addressed through four sets of numerical simulations that calculate a new set of variables defined by D m (t) = ( , giving rise to a suggestion that a depletion of nonlinearity is occurring which could be the cause of Navier-Stokes regularity. The first simulation is of very anisotropic decaying turbulence; the second and third are of decaying isotropic turbulence from random initial conditions … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(68 citation statements)
references
References 39 publications
2
66
0
Order By: Relevance
“…First, nearly continuous higher-order vorticity moments and their production terms were saved at run-time for most of the major calculations. Using this data, the higher-order vorticity moment analysis of Donzis et al (2013) and Kerr (2013b) can be repeated to see if this alternative picture of the t r t t x colllapse yields new hints for the origins and generality of the B ν (t) (1.1) scaling. Then, to find what connects the distant periodic boundaries to the evolving compact structures, the diagnostics introduced by Kerr (2017) should be applied to all of the ν 3.125-e5 trefoil calculations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…First, nearly continuous higher-order vorticity moments and their production terms were saved at run-time for most of the major calculations. Using this data, the higher-order vorticity moment analysis of Donzis et al (2013) and Kerr (2013b) can be repeated to see if this alternative picture of the t r t t x colllapse yields new hints for the origins and generality of the B ν (t) (1.1) scaling. Then, to find what connects the distant periodic boundaries to the evolving compact structures, the diagnostics introduced by Kerr (2017) should be applied to all of the ν 3.125-e5 trefoil calculations.…”
Section: Discussionmentioning
confidence: 99%
“…This was done by determining higher-order vorticity moments ω L p ℓ , which when rescaled as suggested by (Gibbon 2010(Gibbon , 2012 are invariably inversely ordered from the Hölder (5.2) expectation (Donzis et al 2013). The case where this ordering is strongest is an earlier version of the anti-parallel calculation here.…”
Section: Self-similar Anti-parallel Collapsementioning
confidence: 99%
See 1 more Smart Citation
“…This becomes stronger as m increases. Two new related papers are Kerr (2013), which shows the details of the physical space structures responsible for the D m (t) fluctuations in figure 2, and Donzis et al (2013), which shows that this hierarchy is found for all the Navier-Stokes simulations it has been tested on, including forced and decaying isotropic calculations.…”
Section: Applying the D M To Numerical Datamentioning
confidence: 95%
“…Such depletion is a well-documented phenomenon for both Euler and Navier-Stokes cases [1,6,17,21,24,30,31,34]. The question is how to capture and exploit this favourable phenomenon in a rigorous manner.…”
Section: Introductionmentioning
confidence: 99%